Pendampingan Penyusunan Laporan Keuangan Oleh PT Arrasyid Trio Konsultindo Menggunakan Software Accurate Pada Pelaku UMKM - Anissa Eka Safitri; Sudiyanto Sudiyanto (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2024)
Micro Small and Medium Enterprises (MSMEs) are economic activities whose business scope is still in the small category and is usually only managed by individuals. PT Arrasyid Trio Konsultindo is the subject of this activity which acts as a financial and management consultant. The location of the implementation of mentoring activities is in 2 (two) places, namely the client PT Arrasyid Trio Konsultindo's office in Madiun, East Java and at the official office which is located at Perum Zada Regency 1, Block 11, RT 03 / RW 09, Bulakan, Sukoharjo, Central Java. CV. Argo Mulyo Sejahtera is the client who uses financial statement preparation assistance services. There are the problem encountered by CV. Argo Mulyo Sejahtera is the unavailability of financial reports that are systematic and aligns with financial accounting standard MSMEs (SAK EMKM). The purpose of the mentoring activities carried out by PT Arrasyid to CV. Argo Mulyo Sejahtera is to present more valid, effective and efficient financial statements. The methods used are observation and preparation, providing workshops on the importance of financial reports and Accurate Software, as well as monitoring and mentoring MSMEs. The results of the Financial Report Preparation Assistance are that MSME actors can find out how to prepare financial reports using Accurate software easily and efficiently.